The Early Psychosis Intervention Center (EPICENTER): development and six-month outcomes of an American first-episode psychosis clinical service. Issue 1 (December 2015) - Breitborde, Nicholas; Bell, Emily; Dawley, David; Woolverton, Cindy; Ceaser, Alan; Waters, Allison; Dawson, Spencer; Bismark, Andrew; Polsinelli, Angelina; Bartolomeo, Lisa; Simmons, Jessica; Bernstein, Beth; et al.
Abstract Background There is growing evidence that specialized clinical services targeted toward individuals early in the course of a psychotic illness may be effective in reducing both the clinical and economic burden associated with these illnesses. Unfortunately, the United States has lagged behind other countries in the delivery of specialized, multi-component care to individuals early in the course of a psychotic illness. A key factor contributing to this lag is the limited available data demonstrating the clinical benefits and cost-effectiveness of early intervention for psychosis among individuals served by the American mental health system. Thus, the goal of this study is to present clinical and cost outcome data with regard to a first-episode psychosis treatment center within the American mental health system: the Early Psychosis Intervention Center (EPICENTER). Methods Sixty-eight consecutively enrolled individuals with first-episode psychosis completed assessments of symptomatology, social functioning, educational/vocational functioning, cognitive functioning, substance use, and service utilization upon enrollment in EPICENTER and after 6 months of EPICENTER care. All participants were provided with access to a multi-component treatment package comprised of cognitive behavioral therapy, family psychoeducation, and metacognitive remediation. Results Over the first 6 months of EPICENTER care, participants experienced improvements in symptomatology, social functioning, educational/vocational functioning, cognitive functioning, and substance abuse. The average cost of care during the first 6 months of EPICENTER participation was lower than the average cost during the 6-months prior to joining EPICENTER. These savings occurred despite the additional costs associated with the receipt of EPICENTER care and were driven primarily by reductions in the utilization of inpatient psychiatric services and contacts with the legal system. Conclusions The results of our study suggest that multi-component interventions for first-episode psychosis provided in the US mental health system may be both clinically-beneficial and cost-effective. Although additional research is needed, these findings provide preliminary support for the growing delivery of specialized multi-component interventions for first-episode psychosis within the United States. Trial registration ClinicalTrials.gov Identifier:NCT01570972 ; Date of Trial Registration: November 7, 2011